Workers with Ehlers-Danlos syndrome: health surveillance and suitable job assignment - Bogni, Monica; Bassotti, Alessandra; Leocata, Giuseppe; Barretta, Francesco; Brunani, Amelia; Bertazzi, Pier Alberto; Riboldi, Luciano; Vigna, Luisella Maria (La Medicina del Lavoro, 2015)
Backgrounds: In Europe 23.5% of the working-age population suffers from chronic or rare diseases, including Ehlers-Danlos syndrome (EDS), an inherited disorder of the connective tissue that frequently leads to impairment also at work. Objectives: We sought to evaluate the impairment of different functional areas in EDS subjects, using EDS-Disability Test (EDS-DT) (7 visual analogical scales: pain, stiffness, daily activities of life, in the home, outside the home, at work, in social relationships). Methods: We administered the EDS-DT to 50 workers with EDS (classic type n=35, hypermobile n=14, vascular n=3) and 150 healthy workers (non-EDS). Results: EDS subjects showed higher perceived disability (median 29.31 vs 7.22, p< 0.0001) than non-EDS. We observed a trend suggesting that the hypermobile type has a higher level of pain (54 vs 42) and work impairment (62.5 vs 42.5) (p>0.20), whereas the classic type has greater impairment of daily living activities (18.57 vs 11.43) and in the home (34.29 vs 25.71) (p>0.20). Subjects reporting moderate-to-vigorous occupational physical activities (OPA) showed a higher disability level in the work area (p=0.04). Conclusions: People with EDS suffer from chronic pain, impaired quality of life and employment difficulties. The hypermobile type seems more compromised in functional areas such as pain and work, while the classic type is more compromised in daily routine and home activities. The employment section was more impaired for EDS subjects who perform tasks with greater physical effort.